The role of 18F-FDG PET/CT in detecting rare post-surgical cardiac metastasis of metaplastic breast carcinoma: a case report - Liao, Taiping; Fu, Guoxu; Li, Lingxiao; Qi, Qinlin; Li, Li; Long, Yongjun (Frontiers in Oncology, 2025)
Metaplastic carcinoma of the breast is an extremely rare and highly aggressive malignancy associated with a poor prognosis. Breast spindle cell carcinoma is a subtype of metaplastic carcinoma. We present the case of a 48-year-old woman who was found to have a breast nodule during a routine examination two years ago. Pathological examination following surgical resection confirmed the diagnosis of breast spindle cell carcinoma. One year later, a follow-up CT scan detected a progressively enlarging mass in the left lower lobe of the lung, which was histologically confirmed as metastatic breast spindle cell carcinoma after surgical excision. Recently, the patient developed chest discomfort and severe left thigh pain, prompting an18F-FDG PET/CT scan, which revealed metastases to the lung, heart, pleura, and femur. Subsequently, the patient’s condition deteriorated rapidly within a short period. This report highlights the rare imaging findings of cardiac metastasis following surgery for breast spindle cell carcinoma, underscoring the highly aggressive nature of this tumor and the pivotal role of18F-FDG PET/CT in the post-operative monitoring of patients with breast spindle cell carcinoma.